2021
DOI: 10.1001/jamanetworkopen.2021.5686
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Burnout Associated With Sex, Clinician Type, Work Culture, and Use of Electronic Health Records

Abstract: Key Points Question What is the association of clinician sex, use of the electronic health record (EHR), and work culture with clinician burnout? Findings This cross-sectional study of 1310 clinicians found burnout to be more prevalent in women, attending physicians, and advanced practice providers. Multivariate modeling of burnout identified local work culture accounting for 17.6% variance compared with only 1.3% variance for EHR metrics. Female sex indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 42 publications
3
53
0
Order By: Relevance
“…Some important issues are caused by power and subordination relationships that exist in the professional sector, such as moral and gender harassment, wage inequality, and discrimination regarding work capacity; such issues may affect women’s QOL. Notably, advances in labor legislation have not been able to reverse these gender inequalities [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some important issues are caused by power and subordination relationships that exist in the professional sector, such as moral and gender harassment, wage inequality, and discrimination regarding work capacity; such issues may affect women’s QOL. Notably, advances in labor legislation have not been able to reverse these gender inequalities [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a survey study of 1310 ambulatory clinicians, which found that work culture explained more variation in burnout than the EHR ( R 2 , 17.6% vs 1.3%; P < .001). 33 Similarly, physician-perceived EHR usability explained only 5.8% of burnout. 17 Although 2 recent physician surveys reported that excessive EHR time was the most prevalent stressor associated with burnout (OR, 1.99; 95% CI, 1.21-3.27) 34 and that physicians who were frustrated with their EHR had 2.4 times higher odds of burnout (95% CI, 1.6-3.7; P < .001), 35 the findings from the present analysis suggest either a smaller contribution of the EHR to physician turnover or a more complex relationship between EHR use, burnout, and attrition.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies showed that female physicians had a higher prevalence of burnout from countries including America, China, Sweden, Nigeria, etc. ( Norlund et al, 2010 ; Dyrbye et al, 2011 ; Aguwa et al, 2014 ; Granek et al, 2016 ; Huang et al, 2019 ; Eden et al, 2020 ; Gold et al, 2021 ; Lee et al, 2021 ; McPeek-Hinz et al, 2021 ). A few other studies reported only marginal gender differences in physician burnout prevalence ( Linzer et al, 2002 ; te Brake et al, 2003 ; Śliwiński et al, 2014 ; El Ghaziri et al, 2019 ; Doraiswamy et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have used the Shirom Melamed Burnout Questionnaire ( Norlund et al, 2010 ), Freudenberger Burnout Scale ( Aguwa et al, 2014 ), Mini-Z burnout scale ( Gold et al, 2021 ), Utrechtse Burnout Schaal ( te Brake et al, 2003 ), or Burnout Scale Inventory ( Śliwiński et al, 2014 ). Others used one or two items to measure burnout ( Granek et al, 2016 ; El Ghaziri et al, 2019 ; Eden et al, 2020 ; McPeek-Hinz et al, 2021 ). Huang et al used a 7-point Likert scale for MBI-HSS, ranging from 1 to 7, instead of 0 to 6 ( Ma et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation